Evaluation of Students’ Opinions on Mathematics Teaching Process Designed According to Multiple Intelligence Theory - Kutluca, Tamer; Laçin, Seval; GUNDUZ, Samet (Journal of Arts & Social Sciences, 2020)
In this research, it is aimed to introduce the teaching process related to the mathematics course designed according to multiple intelligence theory and to evaluate the students’ opinions about the teaching process. Action research design was used in the research. Purposeful sampling method was used in the research group. The research group consisted of 18 students attending a high school. As a result of the evaluation of the observation forms applied, the students developed materials and activities related to their own intelligence areas related to trigonometry. The interview form was analyzed with descriptive analysis method. As a result of the research, it was determined that the students stated that the lessons were more fun and they learned the subject more easily with the activities designed according to multiple intelligence theory. It was concluded that the students learned by doing by themselves because they prepared the materials themselves, they participated in the classes more actively but the application process took too much time and the learning environment was noisier.